Lyt og deltag! - Hörspielmacher Paul Plampers værker - Pinto, Vito (Peripeti, 2015)
In this paper, Vito Pinto presents some general theories about how to perceive radio plays by focusing on the different listening modes. He then relates these ideas to three exemplary works of the German Hörspielmacher Paul Plamper. Moreover, he concentrates on the particular staging of the voices and the evolvement of the spatiality therein as being the key factors for an understanding of the listener’s perceptive and participatory process and its aesthetic impact.